2008
DOI: 10.1128/jmbe.v9.92
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Evaluation of an Online Microbiology Course for Nonscience Majors

Abstract: The development of web-based technologies provides a new method for course delivery. As with any new technique, evaluation is a necessary tool to determine if the method is consistent with expectations. This study describes the conversion of a nonscience majors' microbiology lecture course to online delivery and evaluates the hypothesis that the online course can be as effective as the traditional course. Course examination scores are compared between the face-to-face and online sections over a 3-year period. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…One of the few studies with biology majors was conducted at a community college and found that traditional-age students performed just as well in face-to-face versus online biology courses, but that performance of non–traditional age students was worse in online biology courses (Garman, 2012). Online biology courses for nonmajors are more common, and several studies found no impact of moving these courses online for student learning outcomes relative to a traditional lecture-based face-to-face course (Johnson, 2002; Hughes, 2008; Hauser, 2016). Thus, there is not a consensus in the literature about the merits of online courses versus traditional face-to-face courses for biology majors.…”
Section: Introductionmentioning
confidence: 99%
“…One of the few studies with biology majors was conducted at a community college and found that traditional-age students performed just as well in face-to-face versus online biology courses, but that performance of non–traditional age students was worse in online biology courses (Garman, 2012). Online biology courses for nonmajors are more common, and several studies found no impact of moving these courses online for student learning outcomes relative to a traditional lecture-based face-to-face course (Johnson, 2002; Hughes, 2008; Hauser, 2016). Thus, there is not a consensus in the literature about the merits of online courses versus traditional face-to-face courses for biology majors.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of an entire face-to-face microbiology course to one being all online has been done for nonbiology majors in a hospitality management university (15). To construct the course, faculty had to adapt the lectures into a written format and add appropriate visual aids, such as short videos and Flash animation.…”
Section: Adult Online Microbiology Coursesmentioning
confidence: 99%
“…For that reason, many professors do not have the expertise required to organize and run online courses and have been struggling to adapt their in-person courses to remote teaching ( 9 , 11 ). Online educational and professional development courses are well recognized as effective in delivering knowledge to students and other intended audiences ( 1 , 12 , 13 ). However, there are still many challenges in making online courses engaging and effective in delivering information.…”
Section: Introductionmentioning
confidence: 99%